2015
DOI: 10.3390/nano5010090
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances on Carbon Nanotubes and Graphene Reinforced Ceramics Nanocomposites

Abstract: Ceramics suffer the curse of extreme brittleness and demand new design philosophies and novel concepts of manufacturing to overcome such intrinsic drawbacks, in order to take advantage of most of their excellent properties. This has been one of the foremost challenges for ceramic material experts. Tailoring the ceramics structures at nanometre level has been a leading research frontier; whilst upgrading via reinforcing ceramic matrices with nanomaterials including the latest carbon nanotubes (CNTs) and graphen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 140 publications
(62 citation statements)
references
References 109 publications
2
56
0
1
Order By: Relevance
“…In recent years, some studies have demonstrated that the introduction of graphene can remarkably enhance the mechanical properties of ceramic and cement composites [36,37,38]. It is a key precondition for higher reinforcement of GNP–cement composite to disperse GNPs into cement matrix uniformly.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, some studies have demonstrated that the introduction of graphene can remarkably enhance the mechanical properties of ceramic and cement composites [36,37,38]. It is a key precondition for higher reinforcement of GNP–cement composite to disperse GNPs into cement matrix uniformly.…”
Section: Discussionmentioning
confidence: 99%
“…It's worth noting that the best interface strength is not the strongest but the most appropriate. Some weak and strong interfaces are unable to reinforce ceramics [33,69,70].…”
Section: Interface Mechanism Of Nanocarbon Reinforced Ceramic Matrix mentioning
confidence: 99%
“…Earlier attempts to produce Al 2 O 3 -based composites containing ceramic or metallic whiskers, fibers or particulates could not satisfy the requirement of their direct use as structural components [5,6]. Incorporation of carbon nanotubes (CNT) into Al 2 O 3 has, to a certain extent, led to improvements in toughness, strength and other mechanical properties in recent years [7][8][9][10][11]. However, the exceptional strength and elasticity associated with onedimensional CNT still could not be fully exploited for Al 2 O 3 due to technical challenges including CNT agglomeration, inadequate densification processes and poor Al 2 O 3 /CNT interfacial strength [12][13][14].…”
Section: Introductionmentioning
confidence: 99%